(untitled) (RevistAleph, 2014)
Resumo: Neste artigo, apresentamos e descrevemos vestígios encontrados acerca do ensino de Matemática no RN, durante a década de 1970, relacionados à Matemática Moderna. Estes vestígios foram evidenciados no curso para professores da Escola Normal que houve em Natal/RN (1971), bem como nas aulas de Matemática no Colégio Atheneu (1970). Para elaborar esta história, respaldamo-nos em pressupostos teóricos da História Cultural. Analisamos as fontes escritas e orais que utilizamos, classificamos os documentos e empregamos a intertextualidade, buscando regularidades e distanciamentos entre as fontes. PALAVRAS-CHAVE: Ensino. Matemática Moderna. Escola Normal. Abstract: In this article, we present and describe traces found on the teaching of Mathematics in RN, during the 70’s, related to Modern Mathematics. These traces were detected in the course for Teachers in Normal Schools who were in Natal/ RN (1971), as well as in mathematics classes at the College Atheneu (1970). To elaborate this story, we used as theoretical foundation assumptions of Cultural History. We analyzed the written and oral sources we used, classified documents and used intertextuality, seeking regularities and differences between the sources. KEY-WORDS: Teaching. Modern Mathematics. Normal School.